Aplikasi Teknologi QR Code Pada Identifikasi Tumbuhan Di Wisata De-Djawatan - Fathul Hadi, Charis; Mustika Yasi, Ratna; agustin, cici (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2022)
De-Djawatan Tourism Destinations are known by various tourists both local and non-local with their natural beauty in the form of large and lush trees that are still beautiful or natural. De-Djawatan tourism does not yet have detailed information either manually or digitally related to the biological and general classification of plants in that location. As smartphone technology develops, the information needed to be very easy to obtain. QR Code is one method to obtain complete information. QR Code is a type of two-dimensional image that displays data in the form of text. This community partnership program aims to provide appropriate technology in the form of the QR code method in determining the identification of plants found in De-Djawatan tourist destinations. This aims to make it easier for tourists to find information on various plants both biologically and in general. The stages of program implementation start from the observation stage, media creation, and implementation. The results of this program using the QR Code can include the identity of the identification results of plants, such as division, order, family, genus and species of plants in the De-Djawatan location. In this QR Code method there are features such as Home, Collection, and Admin. Before the QR Code is created, the document data is encrypted and then used as a QR Code. The result of scanning the QR Code is in the form of a Uniform Resource Locator (URL) that points to the document data. When the URL is executed on the web browser, the system performs a description of the URL, then it is matched with the database, and then displayed to the web browser. The final result is a Document Validation application in the form of a QR Code which is used to convey plant identification information, such as division, order, family, genus and species of plants.